Effects of Water-Based Contrast Media on Experimentally Induced Established Atherosclerotic Plaques in Rabbits - M., Kaur; T, Rahman; NK, Mohd Kornain; R, Ahmad; R, Awang Jalil; MR, Isa; N, Mohd Noor; H, Nawawi (IIUM Medical Journal Malaysia, 2020)
INTRODUCTION: Imaging techniques involving optical coherence tomography, computed tomography (CT) and high-resolution magnetic resonance imaging (MRI) are used as tools to identify atherosclerotic plaques. However, the effects of water-based contrast media used in Post Mortem Computed Tomography Angiography (PMCTA) on the histopathology of atherosclerotic plaques have not been widely explored. The objective of this study is to determine the effects of water-based contrast media used in PMCTA on the histopathology of atherosclerotic plaques and biomarkers of atherosclerosis in experimentally induced established atherosclerotic rabbits. MATERIALS AND METHODS: Twenty male New Zealand white rabbits were divided into 2 groups. One group was given a high cholesterol diet (HCD) for 12 weeks to establish atherosclerosis and the control group normal diet (ND). Five rabbits from each group were then given intravenous water-based contrast media before being sacrificed. The entire length of aorta was dissected and submitted for histopathological examination and determination of tissue biomarkers α-SMA and MMP-9. RESULTS: Histopathological examination of the aorta including percentage of area covered by plaque and foam cell formation showed no significant difference in atheromatous plaque formation in both groups of HCD rabbits with or without intravenous contrast media injection (plaque: 55±41 vs. 63±15, p=0.731; foam cells: 124±83 vs. 171±55, p=0.325). Similarly, α-SMA and MMP-9 protein expression also showed no significant difference in both groups (α-SMA: 70±20 vs. 67±26, p=0.807; MMP-9: 60±12 vs. 57±17, p=0.785). CONCLUSION: Water-based contrast media used in PMCTA does not affect the morphology or the immunohistochemistry staining of SMA and MMP-9 in atherosclerotic plaques.